EFFECT OF NICOTINE IN CIGARETTE FOR TYPE 2 DIABETES MELLITUS - Ario, M Dwi (Majority, 2014)
Abstract Smoking is one of the habits of the people nowadays that can cause health problems. One of disease resulted from exposure to cigarette smoking is type 2 Diabetes Mellitus (DM). Nicotine, known as the main active part in cigarettes is responsible for the association between cigarette smoking and development of type 2 DM, followed by role of the nicotinic acetylcholine receptors (nAChRs) and other complex potential mechanisms. The effect of nicotine on insulin such as decrease insulin release, negatively affect insulin action, impaired pancreatic β–cells and development of insulin resistance. Nicotine has an influence to lead on the development of type 2 DM and smoking cessation is important to improve glucose control in type 2 DM who smoke. Keywords: insulin, nicotine, smoking, type 2 DM Abstrak Merokok merupakan salah satu kebiasaan masyarakat sekarang yang dapat mengakibatkan gangguan kesehatan. Salah satu penyakit yang menjadi faktor resiko penyakit dari paparan asap rokok yaitu Diabetes Melitus (DM) tipe 2. Nikotin yang dikenal sebagai bahan aktif utama pada rokok bertanggung jawab sebagai penyebab dari asap rokok terhadap perkembangan DM tipe 2, diikuti oleh peran nicotinic acetylcholine receptors (nAChRs) dan mekanisme – mekanisme potensial kompleks lainnya. Pengaruh nikotin terhadap insulin yaitu penurunan pelepasan insulin, pengaruh negatif pada kerja insulin, gangguan sel β pankreas dan perkembangan resistensi insulin. Nikotin memiliki pengaruh terhadap perkembangan DM tipe 2 dan berhenti merokok penting untuk memperbaiki kontrol gula pada pasien DM tipe 2 yang merokok. Kata kunci: DM tipe 2, insulin, merokok, nikotin